2021
DOI: 10.1186/s13046-021-02041-2
|View full text |Cite
|
Sign up to set email alerts
|

Statins: a repurposed drug to fight cancer

Abstract: As competitive HMG-CoA reductase (HMGCR) inhibitors, statins not only reduce cholesterol and improve cardiovascular risk, but also exhibit pleiotropic effects that are independent of their lipid-lowering effects. Among them, the anti-cancer properties of statins have attracted much attention and indicated the potential of statins as repurposed drugs for the treatment of cancer. A large number of clinical and epidemiological studies have described the anticancer properties of statins, but the evidence for antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
184
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(185 citation statements)
references
References 313 publications
(269 reference statements)
1
184
0
Order By: Relevance
“…Co-targeting of Wee1 and the DNA damage response kinase ATM was shown to downregulate PD-L1 expression in pancreatic cancer ( 15 ). Wee1 inhibition was found to sensitize cancer cells to immunotherapy via PD-1 checkpoint blockade in oral cavity carcinoma, melanoma and colon adenocarcinoma with variable Tp53 mutations, which provide a pre-clinical rationale for the combination of agents that target cell cycle checkpoints and activate anti-tumor immunity and simultaneously support the clinical trials of Wee1 inhibitor in combination with immunotherapy ( 16 ). The effect of the combination of Wee1 inhibitor ZN-c3 with PD1 inhibitor Pembrolizumab will also be studied in patients with solid tumors with advanced or metastatic disease at the clinical trial NCT04158336.…”
Section: Wee1 Inhibitorsmentioning
confidence: 97%
See 3 more Smart Citations
“…Co-targeting of Wee1 and the DNA damage response kinase ATM was shown to downregulate PD-L1 expression in pancreatic cancer ( 15 ). Wee1 inhibition was found to sensitize cancer cells to immunotherapy via PD-1 checkpoint blockade in oral cavity carcinoma, melanoma and colon adenocarcinoma with variable Tp53 mutations, which provide a pre-clinical rationale for the combination of agents that target cell cycle checkpoints and activate anti-tumor immunity and simultaneously support the clinical trials of Wee1 inhibitor in combination with immunotherapy ( 16 ). The effect of the combination of Wee1 inhibitor ZN-c3 with PD1 inhibitor Pembrolizumab will also be studied in patients with solid tumors with advanced or metastatic disease at the clinical trial NCT04158336.…”
Section: Wee1 Inhibitorsmentioning
confidence: 97%
“…It was later determined that knockout of mevalonate kinase (MVK) has the same effect as reducing mevalonate 5-phosphate, suggesting that the disruption of mutp53 functions may be brought about through targeting and manipulating different parts of the mevalonate pathway ( 18 ). In addition to its effects on mevalonate 5-phosphate, statins inhibit HMG-CoA (HMGCR) reductase activity, which mediates the synthesis of cholesterol and the inhibition of the biosynthesis of selenoproteins (such as GPX4) and CoQ10, and thus enhance ferroptosis ( 11 , 16 , 17 ). Several groups have reported that Hsp90, Hsp40, CHIP and MDM2 play critical roles to stabilize mutant p53 via the HSP chaperone system, which suggests a possible synergism between HSP chaperone system inhibitors and statins in tandem ( 22 , 24 , 25 , 30 ).…”
Section: Mutant P53 and Mevalonate Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…An important observation of great importance for cancer therapy is that statins have an apoptotic effect mainly in the case of neoplastic cells. This means that statins are not destructive in normal cells, as is the case with most drugs used to treat cancer [23][24][25].…”
Section: Introductionmentioning
confidence: 96%